The optical characteristics of contaminating films on Mo, SS and Cu mirror samples exposed in plasma devices - Bondarenko, V.N.; Belyaeva, A.I.; Galuza, A.A.; Konovalov, V.G.; Kudlenko, A.D.; Ryzhkov, I.V.; Shtan’, A.F.; Solodovchenko, S.I.; Voitsenya, V.S. (Вопросы атомной науки и техники, 2008)
The optical methods with the use of in-vessel first mirrors (FMs) are expected to occupy an important place in the diagnostic complex of the future fusion reactor ITER. As the surface of FMs will be subjected to physical sputtering by high-energy D and T charge-exchange atoms, this can lead to a decline in the initial FM reflectance. The second factor of FM reflectance deterioration is the redeposition of contaminants on the mirror surface. In the paper, optical indices and thickness values of the films deposited on Mo and SS mirrors in the tokamak TRIAM-1M as well as on SS and Cu mirrors in the torsatron URAGAN-3M were studied by ellipsometry at the wavelength λ=632.8 nm. The spectral reflectance at normal incidence of light for all the samples was measured in the wavelength range λ=253–650 nm. The optical parameters of TRIAM-1M films were determined as the film was progressively removed by deuterium plasma ions in the stand DSM-2.